Some proposals on the development orientation of science and technology fields in Vietnam in the period of 2021-2030 - Nguyen Hong Anh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
In the science and technology development strategy of any country, the orientation of science and technology development is very important. One of the core issues of the orientation is determining the direction of science and technology development in industries and fields. The development orientation clarifies the objects that need to be focused on development, thereby creating a new scientific and technological situation. Due to limited resources, it is necessary to determine the priority orientation from the general directions, avoid spreading, and should only focus resources on a few industries and fields that have advantages and bring about the highest possible efficiency. Appropriate to the context and actual conditions of each country. The orientations should not only rationally allocate resources but also pay attention to the time factor (short, medium or long term). In the development orientation of the National Strategy for Science, Technology and Innovation Development in the period 2021-2030, it is necessary to clearly define the direction of service for economic development of the fields of social sciences, natural sciences, and technologies. Code: 21122901